Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Does anybody know how to prove this series?

$$\sum_{n=1}^{\infty} \left( n\log \left(\frac{2n+1}{2n-1}\right)-1\right) = \frac{1-\log 2}{2}$$

I arrived at this through Mathematica.

I tried writing $\log \left(\frac{2n+1}{2n-1}\right)$ as $\int_0^1 \frac{1}{\frac{2n-1}{2}+x}dx$ and $-\sum_{k=1}^\infty \frac{(-2)^k}{k(2n-1)^k}$ but none of them worked.

share|improve this question
    
Try $\log((2n+1)/(2n-1))=\log(2n+1)-\log(2n-1)$ ? –  ᴊ ᴀ s ᴏ ɴ Mar 17 '13 at 5:45
add comment

3 Answers 3

up vote 6 down vote accepted

Note that

\begin{align*} \sum_{n=1}^{\infty}\left(n \log \left(\frac{2n+1}{2n-1}\right) - 1 \right) &=\lim_{N\to\infty} \sum_{n=1}^{N}\left(n \log \left(\frac{2n+1}{2n-1}\right) - 1 \right)\\ &=\lim_{N\to\infty} \log\left[ e^{-N} \prod_{n=1}^{N} \left(\frac{2n+1}{2n-1}\right)^{n} \right] \\ &=\lim_{N\to\infty} \log\left[ e^{-N} \frac{2^{N} N! (2N+1)^{N}}{(2N)!} \right]. \end{align*}

By Stirling's formula, it follows that

$$ e^{-N} \frac{2^{N} N! (2N+1)^{N}}{(2N)!} \sim \sqrt{\frac{e}{2}}. $$

This immediately yields the desired answer.

share|improve this answer
add comment

$$n \log \left(\dfrac{2n+1}{2n-1}\right) = n \left(\log(1+1/2n) - \log(1-1/2n)\right)$$ \begin{align} \log(1+x) - \log(1-x) & = \left(x - \dfrac{x^2}2 + \dfrac{x^3}3 \mp \cdots\right) - \left(-x - \dfrac{x^2}2 - \dfrac{x^3}3 - \cdots\right)\\ & = 2\left(x + \dfrac{x^3}3 + \dfrac{x^5}5 + \cdots \right) \end{align} Hence, $$n \left(\log(1+1/2n) - \log(1-1/2n)\right) = 2n \left(\sum_{k=0}^{\infty} \dfrac1{(2k+1)(2n)^{2k+1}}\right) = \sum_{k=0}^{\infty} \dfrac1{(2k+1)(2n)^{2k}}$$ Hence, $$n \log \left(\dfrac{2n+1}{2n-1}\right) - 1 = \sum_{k=1}^{\infty} \dfrac1{(2k+1)(2n)^{2k}}$$ $$\sum_{n=1}^{\infty} \left(n \log \left(\dfrac{2n+1}{2n-1}\right) - 1\right) = \sum_{k=1}^{\infty} \sum_{n=1}^{\infty} \dfrac1{(2k+1)(2n)^{2k}} = \sum_{k=1}^{\infty} \dfrac{\zeta(2k)}{(2k+1) \cdot 2^{2k}}$$

\begin{align}f(m) & = \sum_{n=1}^m \left(n \log\left(\dfrac{2n+1}{2n-1}\right)-1\right)\\ & = \left( 1\log(3) - 1 + 2 \log(5) - 2 \log(3) + 1 + \cdots \right)\\ & = m - \log(3) - \log(5) - \cdots - \log(2m-1) + m \log(2m+1) \end{align} Now $$\log(1) + \log(3) + \log(5) + \cdots + \log(2m-1) = \log \left(\dfrac{(2m)!}{2^m \cdot m!}\right)$$ Hence, $$f(m) = m + m \log(2m+1) - \log \left(\dfrac{(2m)!}{2^m \cdot m!}\right)$$ Now use Stirling to get your answer.

share|improve this answer
add comment

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $\ds{\sum_{n = 1}^{\infty}\bracks{n\ \ln\pars{2n + 1 \over 2n - 1} - 1} ={1 - \ln\pars{2} \over 2}}$

With ${\ds{\quad N \in {\mathbb N}\,,\quad N \geq 1}}$: \begin{align}&\color{#c00000}{\sum_{n = 1}^{N}n\ \ln\pars{2n + 1 \over 2n - 1}} =\sum_{n = 1}^{N}n\int_{-1}^{1}{\dd x \over x + 2n} =\half\int_{0}^{1}\sum_{n = 1}^{N}\pars{{n \over n + x/2} + {n \over n - x/2}} \,\dd x \\[3mm]&=\half\int_{0}^{1}\sum_{n = 1}^{N} \pars{1 - {x/2 \over n + x/2} + 1 + {x/2 \over n - x/2}}\,\dd x \\[3mm]&=N + {1 \over 4}\int_{0}^{1} x\sum_{n = 1}^{N}{x \over \pars{n + x/2}\pars{n - x/2}}\,\dd x \\[3mm]&=N + {1 \over 4}\int_{0}^{1} x\sum_{n = 0}^{N - 1}{x \over \pars{n + 1 + x/2}\pars{n + 1 - x/2}}\,\dd x \end{align}

$$ \color{#c00000}{\sum_{n = 1}^{N}\bracks{n\ln\pars{2n + 1 \over 2n - 1} - 1}} ={1 \over 4}\int_{0}^{1} x\sum_{n = 0}^{N - 1}{x \over \pars{n + 1 + x/2}\pars{n + 1 - x/2}}\,\dd x $$

\begin{align} &\color{#c00000}{\sum_{n = 1}^{\infty}\bracks{n\ln\pars{2n + 1 \over 2n - 1} - 1}} ={1 \over 4}\int_{0}^{1}x\bracks{% \Psi\pars{1 + {x \over 2}} - \Psi\pars{1 - {x \over 2}}}\,\dd x \\[3mm]&={1 \over 4}\int_{0}^{1}x\bracks{% {2 \over x} + \Psi\pars{x \over 2} - \Psi\pars{1 - {x \over 2}}}\,\dd x =\half - {1 \over 4}\int_{0}^{1}x\pi\cot\pars{\pi x \over 2}\,\dd x \end{align}

$$ \color{#c00000}{\sum_{n = 1}^{\infty}\bracks{n\ln\pars{2n + 1 \over 2n - 1} - 1}} =\half - {1 \over \pi}\color{#00f}{\int_{0}^{\pi/2}x\cot\pars{x}\,\dd x}\tag{1} $$

\begin{align}&\color{#00f}{\int_{0}^{\pi/2}x\cot\pars{x}\,\dd x} =\left.x\ln\pars{\sin\pars{x}}\vphantom{\LARGE A}\right\vert_{0}^{\pi/2} -\ \underbrace{\int_{0}^{\pi/2}\ln\pars{\sin\pars{x}}\,\dd x} _{\ds{-\,{\pi\ln\pars{2} \over 2}}}\ =\ \color{#00f}{{\pi\ln\pars{2} \over 2}} \end{align} The $\ds{\large\ln\pars{\sin\pars{\cdots}}}$-integral is reported by M.SE as a frequent question. Replacing the last result in $\pars{1}$:

$$\color{#66f}{\large% \sum_{n = 1}^{\infty}\bracks{n\ \ln\pars{2n + 1 \over 2n - 1} - 1} ={1 - \ln\pars{2} \over 2}} \approx 0.1534 $$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.